2009
DOI: 10.1002/ijc.24297
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin gene expression levels as potential biomarkers for malignancy of gingival squamous cell carcinoma

Abstract: Accurate assessment of malignancy in oral squamous cell carcinoma is essential to optimize treatment planning. To detect a biomarker related to malignant propensity in gingival squamous cell carcinoma (GSCC), quantitative gene expression analysis of tetraspanin family genes was conducted. In 73 cases of GSCC, total RNA was extracted from carcinoma tissues, and gene expression was analyzed by quantitative real time-PCR. Six tetraspanin family genes (CD9, CD63, CD81, CD82, CD151, NAG-2) were investigated. Housek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In our previous study, we analyzed the ratio of expression of the 11 ITG family genes to that of the 14 functionally related genes; in total, 154 gene expression ratios for 66 tongue SCC cases [15]. We also investigated the potential of 45 tetraspanin family gene expression ratios that were calculated based on 6 tetraspanin family genes with housekeeping functionality or functionally related genes for 73 gingival SCC cases [16]. The results of these prior studies revealed two ITG gene expression ratios–those of ITGA3/CD9 and ITGB4/JUP–as candidate biomarkers for OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we analyzed the ratio of expression of the 11 ITG family genes to that of the 14 functionally related genes; in total, 154 gene expression ratios for 66 tongue SCC cases [15]. We also investigated the potential of 45 tetraspanin family gene expression ratios that were calculated based on 6 tetraspanin family genes with housekeeping functionality or functionally related genes for 73 gingival SCC cases [16]. The results of these prior studies revealed two ITG gene expression ratios–those of ITGA3/CD9 and ITGB4/JUP–as candidate biomarkers for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The α3ÎČ1 integrin complex is a major receptor for laminin 5 [17] and is involved in the maintenance of epithelial integrity, cell proliferation and motility, and survival of migrating keratinocytes through adhesion to extracellular matrix components [21-23]. CD9 is a tetraspanin family molecule, which forms tetraspanin webs (tetraspanin-enriched microdomains) by associating with various partner molecules such as integrins, growth factor receptors, and other tetraspanin molecules, to affect cell adhesion, signal transduction, proliferation, motility, differentiation, and cancer metastasis [16,24-28]. It has been reported that CD9 negatively influences cancer cell motility by regulating the re-organization of the actin cytoskeleton [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the tetraspanins (CD9, CD151, and CD82) have been shown to interact with EGFR, either directly or in conjunction with integrin adhesion receptors (Wang et al , 2007; Park et al , 2009; Deng et al , 2012; Romanska et al , 2012; Odintsova et al , 2013). Furthermore, there is evidence that reduced expression of CD9 (Mhawech et al , 2004; Buim et al , 2010) and CD82 (Imai et al , 2002; Farhadieh et al , 2004), and increased expression of CD151 (Hirano et al , 2009) confers a poor prognosis in head and neck cancer. It is possible, therefore, that these tetraspanins may also have a role earlier in the carcinogenic process.…”
mentioning
confidence: 99%
“…Note Real-time PCR analysis of CD151 gene expression compared to GAPDH was analysed (Hirano et al, 2009). Assessment of protein expression by immunohistochemistry correlated with gene expression however no statistical analyses were performed on protein expression.…”
Section: Gingival Squamous Cell Carcinomamentioning
confidence: 99%